2019
DOI: 10.1016/j.hrthm.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Low complication rates using high power (45–50 W) for short duration for atrial fibrillation ablations

Abstract: BACKGROUND Many centers use radiofrequency (RF) energy at 25-35 W for 30-60 seconds. There is a safety concern about using higher power, especially on the posterior wall.OBJECTIVE The purpose of this study was to examine complication rates for atrial fibrillation (AF) ablations performed with highpower, short-duration RF energy. METHODSWe examined the complication rates of 4 experienced centers performing AF ablations at RF powers from 45-50 W for 2-15 seconds per lesion. In total, 13,974 ablations were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
187
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(206 citation statements)
references
References 11 publications
16
187
2
1
Order By: Relevance
“…Our protocol was effective and safe, despite a much smaller patient number, which is consistent with a recent study by Winkle et al, who reported the complication rates of four experienced centers performing AFib ablation with RF powers of 45‐50 W for 2‐15 seconds per lesion. In this analysis, 13 974 ablations were performed in a total of 10 284 patients.…”
Section: Discussionsupporting
confidence: 90%
“…Our protocol was effective and safe, despite a much smaller patient number, which is consistent with a recent study by Winkle et al, who reported the complication rates of four experienced centers performing AFib ablation with RF powers of 45‐50 W for 2‐15 seconds per lesion. In this analysis, 13 974 ablations were performed in a total of 10 284 patients.…”
Section: Discussionsupporting
confidence: 90%
“…However, HPSD strategies by themselves do not reduce ablation times. This was shown in a recently published multicenter study by Winkle et al where long procedure times and RF times were found despite the use of a heterogeneous HPSD strategy. Baher et al used 50 W for 5 seconds and found similar safety and efficacy with shorter procedure duration, compared with conventional PVI.…”
Section: Discussionmentioning
confidence: 72%
“…Several authors demonstrated the safety of such an approach till 50 W. There are however very few results on the outcomes. Winkle et al confirmed safety in a large heterogeneous multicentric trial. Procedure duration and RF time were significantly longer and showed more variation in this trial than in our single‐center study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…There was widespread concern among the electrophysiologists that it might be too dangerous and result in more complications, especially atrial esophageal fistulas. These concerns have been partially dispelled by a multicenter report on 13 974 ablations done in approximately 10 284 patients including the use of HPSD on the posterior wall . The complications rate was remarkably low, and this has encouraged many to start utilizing HPSD.…”
mentioning
confidence: 99%